Strategic Management Determination: Organizational Culture, Strategic Leadership, Market Dynamics and Strategy Evaluation - Siswono, Safitri (Dinasti International Journal of Management Science, 2025)
The purpose of this literature study is to develop a hypothesis regarding the influence between variables that can be used for further research in the scope of strategic management. The literature review article on strategic management determination: organizational culture, strategic leadership, market dynamics and strategic evaluation is a scientific literature article in the field of strategic management. The approach used in this literature review is descriptive qualitative. The data collection technique is to use a literature study or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous research, each relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Organizational Culture affects Strategic Management; 2) Strategic Leadership affects Strategic Management; 3) Market Dynamics affects Strategic Management; and 4) Strategy Evaluation affects Strategic Management.